2016
DOI: 10.12965/jer.150261
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term aerobic exercise on cardiac structure, stroke volume of the left ventricle, and cardiac output

Abstract: The purpose of this study is to investigate the effect of the long-term aerobic exercises on cardiac structure, left ventricular stroke volume, and cardiac output. To achieve the purpose of the study, a total of 22 volunteers—including 10 people who have continued regular exercises and 12 people as the control group—were selected as subjects. With regard to data processing, the IBM SPSS Statistics ver. 21.0 was used to calculate the mean and standard deviation, and the difference of the means between the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
(24 reference statements)
0
21
0
1
Order By: Relevance
“…Our results suggest positive adaptation to the intervention and the improvement of systemic oxygen delivery. Other studies have also reported significant improvements in an echocardiogram-generated stroke volume as a result of long-term (> 12 weeks) exercise training [28]. The capacity to increase physical activity depends on the ability of the heart to generate adequate cardiac output and the ability of skeletal muscles to utilise the oxygen delivered [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest positive adaptation to the intervention and the improvement of systemic oxygen delivery. Other studies have also reported significant improvements in an echocardiogram-generated stroke volume as a result of long-term (> 12 weeks) exercise training [28]. The capacity to increase physical activity depends on the ability of the heart to generate adequate cardiac output and the ability of skeletal muscles to utilise the oxygen delivered [29].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Altered haemodynamics due to the high volume of circulating blood in obese people lead to larger stroke volumes and subsequent left ventricular dilatation. 17 Compensatory hypertrophy may develop as a result, thus impairing the diastolic or both systolic and diastolic ventricular functions. 18,19 Pascual et al revealed that the obese children had subclinical left ventricular diastolic dysfunction in all grades of obesity and disturbed systolic functions in the early stages of obesity, which were reversible with weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…SV increased in rest and workload but was significantly in workload. Aerobic exercise for a long time can affect the parasympathetic nerve, thus increasing SV and reducing the resting HR [3,5,35]. Increase in SV due to increases in ventricular end-diastolic volume and due to reductions in endsystolic volume [31].…”
Section: Discussionmentioning
confidence: 99%